Is There God in Postmodern Accounting? - Patricia Widianingsih, Luky; Kohardinata , Cliff (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
The postmodern ethos is pervasive in various aspects including education, accounting in particular. This is certainly a challenge for the practice of education as what is ultimately given to students. The purpose of this study is to reflect on how accounting students interpret several terminologies that are closely related to their professional world in the postmodern world. The research site was conducted during the learning process of the Management Accounting course. The participants involved were nine students. The reflection session is carried out in the last two weeks before the end of the semester. The results of the students' reflections were analyzed reflectively by the researcher. The expressed and implied meanings of their reflection stories are fully understood, including how they express and convey them in front of other class participants. Researchers make memos, note important meanings, categorize them to compile findings and present them as a final synthesis of meaningful findings. This process is like the spiral data analysis for a qualitative study. The findings found that the students have tried to integrate their faith and beliefs in God’s sovereignty in the search for worldly knowledge accounting. The findings of this study indicate that during the challenges of the postmodern world, the students who participated in this study were still able to show traces of their spiritual and religious meaning expressions in looking at several issues that are closely related to the reality of their future profession.